(untitled) (American Journal of Pedagogical and Educational Research, 2023)
Language has always been important. Its importance has increased especially in the age of information and innovative technologies - the new century. In order to be aware of the achievements of science, to master modern techniques and equipment used in various fields, and to use the rich experience of foreign experts, we are required to know at least two or three foreign languages. These aspects are analyzed in the article.